Screening of traditional scented rice (Joha) of Assam for presence of Badh2, blast and brown spot diseases - Chetia, S K; Hazarika, Gongotri; Bordoloi, Sunayana; Talukdar, Manjeet; Tamuly, Amrit; Das, B C; Ali, S; Ahmed, T (ORYZA-An International Journal of Rice, 2019)
The traditional scented rice (Joha) varieties are very popular among the people of Assam. The traditional scented rice though carries a premium price throughout the world, is a low yielder. However, the traditional Joha varieties are tolerant to many disease and pest, indicating the joha germplasm may be a source for several disease/pest resistant genes. However not much work has been carried out to identify the factors responsible for disease/pest tolerance in these lines. Hence, an attempt was made in 39 Joha germplasms to identify blast and brown spot resistant/tolerant germplasms at Regional Agricultural Research Station, Assam Agricultural University, Titabar. In most of the aromatic lines the aroma is due to the function of the Badh2 gene. Therefore, an attempt was made to study the action of Badh2 gene in these germplasms with the help of SNP analysis. The present study reveals the associated between Badh2 gene fragrance in most of the Joha germplasms. However in some aromatic Joha germplasms the fragrance is not correlated with the action of Badh2, and it may be due to some other factors. This finding needs further studies to identify the factors contributing to the fragrance in Joha rice.